A contingency framework for effective information systems design and e-business applications. (29th December 2008) - Boulianne, Emilio
Although e-business is considered a major aspect in achieving higher business performance, a review of refereed journals has shown that there are few conclusive empirical data resulting from e-business research. We therefore have only limited understanding of how to design Information Systems (IS) and associated e-business applications to achieve higher business performance. Without a deeper understanding of these issues, the inappropriate design and implementation of IS and e-business results in project failure and the waste of resources. To deal with the issue of improving business operations, both executives and researchers have pointed out the importance of aligning e-business applications with appropriate business contexts. The present paper, therefore, suggests a comprehensive contingency framework that summarises those contexts in which certain types of IS design and e-business applications are reported to be effective. This theoretical framework is intended to encourage and provide guidance for future research in e-business and designed to be of use to IS designers and adopters. The paper also provides research propositions to examine empirically within an appropriate contingency fit approach, since to different perspectives of fit correspond specific theoretical interpretations and statistical tests.